2011
DOI: 10.1016/j.msec.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Sulphonamide-imprinted sol–gel materials as ionophores in potentiometric transduction

Abstract: This work proposes different kind of solid-contact graphite-based electrodes for the selective determination of sulphonamides (SPHs) in pharmaceuticals, biological fluids and aquaculture waters. Sulfadiazine (SDZ) and sulfamethoxazole (SMX) were selected for this purpose for being the most representative compounds of this group. The template molecules were imprinted in sol-gel (ISG) and the resulting material was used as detecting element. This was made by employing it as either a sensing layer or an ionophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…In particular, progressive polycondensation reactions of molecular precursors in a liquid medium allow the construction of an oxide network. The most common precursors are tetramethyl- and tetraethylorthosilicate [ 300 , 301 ]. Molecular imprinting of sol–gel thin films is advantageous over organic-polymers, because of its easy preparation, low non-specific adsorption and high association constants.…”
Section: Mims-based Bio-mimetic Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, progressive polycondensation reactions of molecular precursors in a liquid medium allow the construction of an oxide network. The most common precursors are tetramethyl- and tetraethylorthosilicate [ 300 , 301 ]. Molecular imprinting of sol–gel thin films is advantageous over organic-polymers, because of its easy preparation, low non-specific adsorption and high association constants.…”
Section: Mims-based Bio-mimetic Sensorsmentioning
confidence: 99%
“…As example, Fireman-Shoresh et al demonstrated the chiral imprintability of spin coated submicron composite sol–gel films (∼700 nm) and their enantioselectivity under steady-state conditions for various enantiomers [ 302 , 303 ]. Sol-gel imprinted membranes were prepared by Almeida et al [ 301 ] that imprinted the antibiotics sulfadiazine (SDZ) and sulfamethoxazole (SMX) in sol-gel materials which were used as sensing elements included in the matrix of poly(vinyl chloride)-based membranes connected to a potentiometric transducer. SDZ is used to treat toxoplasmosis and to put off some type of meningococcal meningitis.…”
Section: Mims-based Bio-mimetic Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almeida et al [ 64 ] proposed the construction of sulfadiazine and sulfamethoxazole selective electrodes based on imprinted sol-gel (ISG) material. The ISG was employed as the electroactive material on PVC membranes selective for sulfadiazine and sulfamethoxazole, prepared by the inclusion of ISG particles into the PVC matrix.…”
Section: Advanced Polymeric Membranes: Synthesis and Applicationsmentioning
confidence: 99%
“…Nevertheless, they are not highly selective to individual members of sulfanilamide class in real media. For the sulfanilamide determination, ionophores based on molecularly imprinted polymers (MIPs) [31][32][33] are also developed. However, there are drawbacks of MIPs, such as the difficulty of the bound analyte extraction, the difference in the constants of the repeated interaction of analyte and reactive centers, and its non-specific binding to the matrix material [34].…”
Section: Introductionmentioning
confidence: 99%